Neuroprotective effect of red quinoa seeds extract on scopolamine-induced declarative memory deficits in mice: The role of acetylcholinesterase and oxidative stress - Sirlei Patricia Souza (Journal of Functional Foods, 2020)
The effect of red quinoa seed extract obtained by soxhlet (RQ-S) on scopolamine (SCP)-induced memory deficits in the object recognition task in mice was evaluated, as well as the involvement of oxidative stress and AChE activity. Four quinoa extracts were obtained: two from white quinoa and two from red quinoa, extracted by soxhlet or shaking. The content of total phenolic compounds (TPC), total flavonoids (TF) and antioxidant activity was determined in the four extracts. The RQ-S showed the highest TPC and TF content and antioxidant activity compared with the others quinoa extracts. The administration of RQ-S prevented memory deficit, changes of AChE activity and oxidative stress indicators (SOD, catalase, TBARS and ROS) induced by SCP, in the hippocampus and partially in the cerebral cortex. These results provide evidence that RQ-S is an alternative to protect SCP-induced memory deficits in mice, and suggest the involvement of oxidative stress and AChE activity.